Marketing activities of enterprises in the express delivery market of Ukraine - Косар, Н. С.; Кузьо, Н. Є.; Косар, О. І.; Kosar, N. S.; Kuzo, N. Ye.; Kosar, O. I. (Видавництво Львівської політехніки, 2023)
Встановлено, що основними факторами, які сприяли зростанню попиту на послуги експрес-доставки в Україні є збільшення користувачів Інтернету, зменшення вільного часу українців, прагнення його оптимізувати, зростання обсягів роздрібної торгівлі. Проаналізовано вплив війни на роботу деяких вітчизняних служб та сервісів доставки – служби доставки їжі Bolt Food, сервісів Glovo, Liki24, служби доставки "Нова Пошта" та Meest Express. Подано особливості інструментарію комплексу маркетингу компаній у сфері послуг. Значні можливості для його вдосконалення відкривають новітні інформаційні технології, зокрема Big Data, штучний інтелект, а також технології машинного навчання. Вони дозволяють зібрати необхідну інформацію для розроблення інструментів комплексу маркетингу компанії, що займається експрес-доставкою, адаптованих до потреб окремих сегментів ринку.

It was established that the main factors that contributed to the growth of express delivery services demand in Ukraine are the development of the Internet in Ukraine and the increase of its users, the decrease in the free time of Ukrainians, the desire to optimize it, and the growth of retail trade. The main companies that provide express delivery services include "Nova Poshta", "Ukrposhta", Meest, Justin, Delivery Auto, Epicenter, and Kasta. It was determined that the most famous brand is the "Nova Poshta" company, which also has the largest number of points of contact with consumers, although Justin company fulfills orders the fastest. The results of office research indicate that the most optimal ratio in terms of price-quality indicators is typical for the company "Ukrposhta" and Justin. In the express delivery market, the biggest threat to postal operators is retail trade networks, which are actively developing their delivery of goods. At the same time, services focused on new market segments also appear. Domestic services and delivery services were significantly affected by the full-scale war. However, the express delivery market quickly recovered from the shock and partially recovered. The impact of the war on the work of some domestic services and delivery services – Bolt Food, Glovo, Liki24, "Nova Poshta", and Meest Express delivery services – was analyzed. The formation of competitive advantages of operators in the market of express delivery services can be ensured by their comprehensive use of tools of the marketing complex, and the formation of co-branding departments. The article presents the features of the toolset of the marketing complex of companies in the service sector. When developing strategies for the development of services and delivery services, the latter must take into account the needs and behavior of consumers. Therefore, it is important to provide information for the marketing activities of companies. New information technologies, including Big Data, artificial intelligence, and machine learning technologies open up significant opportunities for its improvement. They allow you to collect the necessary information for the development of tools for the marketing complex of the express delivery company, adapted to the needs of individual market segments.
Маркетингова діяльність підприємств на ринку експрес-доставки України
Keywords: ринок послуг експрес-доставки; роздрібна торгівля; маркетингова діяльність; вітчизняні служби та сервіси доставки; конкурентні переваги; інструменти комплексу маркетингу; інформаційне забезпечення; вплив війни; market of express delivery services; retail trade; marketing activity; domestic services and delivery services; competitive advantages; tools of the marketing complex; information support; influence of war; 658.8; 338.4; 339.166.8